2008
DOI: 10.1002/cncr.23622
|View full text |Cite
|
Sign up to set email alerts
|

Screening and referral for psychosocial distress in oncologic practice

Abstract: BACKGROUND. The objectives of this study were to validate the Distress Thermometer (DT) in the Netherlands and to examine its correspondence with a 46‐item Problem List, possible risk factors, and the wish for a referral. METHODS. A cross‐sectional group of 277 cancer patients who were treated at 9 hospitals filled in the DT and the Hospital Anxiety and Depression Scale and rated the presence and severity of problems (response rate, 49%). RESULTS. Receiver operating characteristic analyses identified an ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
359
6
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(409 citation statements)
references
References 37 publications
30
359
6
8
Order By: Relevance
“…A large recent review concluded that no specific screening tool for distress could be recommended [20]. A screening tool which is often used in Dutch hospitals, the distress thermometer (Lastmeter) [26], uses dichotomized questions such as 'do you feel distressed', supplemented with the amount of distress on a scale from 0 to 10. A review including seven randomized trials showed that screening showed an effect on psychological well-being in four of the seven trials [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large recent review concluded that no specific screening tool for distress could be recommended [20]. A screening tool which is often used in Dutch hospitals, the distress thermometer (Lastmeter) [26], uses dichotomized questions such as 'do you feel distressed', supplemented with the amount of distress on a scale from 0 to 10. A review including seven randomized trials showed that screening showed an effect on psychological well-being in four of the seven trials [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, screening seems to improve communication between health care providers and patients and may enhance psychosocial referrals and facilitate discussions about QoL [20]. However, it is important to be aware that not all patients with a high level of PD want to be referred for an intervention [26]. In a study in 302 cancer patients in Total number of responding paƟents the Netherlands, mostly treated with curative intent, 51% of distressed patients did not need an intervention directly after treatment and 25% were already receiving support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graves et al [7] found that among 333 lung cancer patients, only 22.5% wanted help with their problems and, even in those with a high rate of distress, only 30% wanted help. In a crosssectional study of cancer patients in the Netherlands, Tuinman et al [8] screened 277 patients using the Distress Thermometer (DT) and the Hospital Anxiety and Depression Scale (HADS). Of those who scored above five on the DT, only 14% definitely wanted to be referred for further help, while 29% would consider a referral.…”
Section: Introductionmentioning
confidence: 99%
“…Of those who scored above five on the DT, only 14% definitely wanted to be referred for further help, while 29% would consider a referral. Interestingly, of those with low distress, 5% still wanted to be referred and 13% would have considered a referral [8]. Clearly, expression of help is linked with the acceptability of the treatment on offer.…”
Section: Introductionmentioning
confidence: 99%